Addition of Ezetimibe to statins for patients at high cardiovascular risk: Systematic review of patient-important outcomes - Fei, Yutong; Guyatt, Gordon Henry; Alexander, Paul Elias; El Dib, Regina [UNESP]; Siemieniuk, Reed A.C.; Vandvik, Per Olav; Nunnally, Mark E.; Gomaa, Huda; Morgan, Rebecca L.; Agarwal, Arnav; Zhang, Ying; Bhatnagar, Neera; et al. (Wiley, 2018)
Ezetimibe is widely used in combination with statins to reduce low-density lipoprotein. We sought to examine the impact of ezetimibe when added to statins on patient-important outcomes. Medline, EMBASE, CINAHL, and CENTRAL were searched through July, 2016. Randomized controlled trials (RCTs) of ezetimibe combined with statins versus statins alone that followed patients for at least 6 months and reported on at least one of all-cause mortality, cardiovascular deaths, non-fatal myocardial infarctions (MI), and non-fatal strokes were included. Pairs of reviewers extracted study data and assessed risk of bias independently and in duplicate. Quality of evidence was assessed using the GRADE approach. We conducted a narrative review with complementary subgroup and sensitivity analyses. IMPROVE-IT study enrolled 93% of all patients enrolled in the 8 included trials. Our analysis of the IMPROVE-IT study results showed that in patients at high risk of cardiovascular events, ezetimibe added to statins was associated with i) a likely reduction in non-fatal MI (17 fewer/1000 treated over 6 years, moderate certainty in evidence); ii) a possible reduction in non-fatal stroke (6 fewer/1000 treated over 6 years, low certainty); iii) no impact on myopathy (moderate certainty); iv) potentially no impact on all-cause mortality and cardiovascular death (both moderate certainty); and v) possibly no impact on cancer (low certainty). Addition of ezetimibe to moderate-dose statins is likely to result in 17 fewer MIs and possibly 6 fewer strokes/1000 treated over 6 years but is unlikely to reduce all-cause mortality or cardiovascular death. Patients who place a high value on a small absolute reduction in MI and are not adverse to use of an additional medication over a long duration may opt for ezetimibe in addition to statin therapy. Our analysis revealed no increased specific harms associated with addition of ezetimibe to statins.
Keywords: ezetimibe; lipid; meta-analysis; statins; systematic review